Perspectives on climate information use in the Caribbean - Dookie, Denyse S.; Conway, Declan; Dessai, Suraje (Frontiers in Climate, 2023)
Within research on climate information for decision-making, localized insights on the influences of climate information use remain limited in small and low-income countries. This paper offers an empirical contribution on Caribbean perspectives of climate information use considering current barriers and enablers in the region. We employ thematic analysis of 26 semi-structured interviews with region-focused sectoral experts (including end-users and decision-makers) drawn from climate adaptation, disaster risk reduction, and resilience focused initiatives and institutions. The results reaffirm presence of known barriers, such as the crucial role of finance, but notably we identify a range of interlinked enabling and catalyzing conditions necessary for the effective use of climate information. These conditions include the need for island- and sector- contextualized climate information, the role of international donors, the importance of adequate human resource capacity and presence of loud voices/climate champions, as well as the need for effective political and legislative mandates and for greater co-production. We construct a visualization of respondents' understanding of influencing factor interrelationships. This shows how their heuristics of climate information use for decision-making intricately link with roles for proactive climate champions, and that available finance often reflects donor interests. We end by discussing how these insights can contribute to strategies for more effective climate information use to promote resilience within the region.